Inovasi Strategi Pemasaran Syariah dalam Menghadapi Persaingan Industri Perbankan Nasional pada BTN Syariah Purwokerto - Arzeti Ika Febrianti; Eili Widiyastuti; Hanifah Nabila; Lie Aulia Ulfi; Yuliana Nur Hasnita; Sulasih (CV. KAMPUSA AKADEMIK PUBLISING, 2025)
This study aims to analyze the forms of Islamic marketing strategy innovation implemented by BTN Syariah Purwokerto in facing competition within the national banking industry and to identify its supporting and inhibiting factors. This research employs a qualitative approach using a case study method through in-depth interviews, observations, and documentation. The findings reveal that innovation occurs in three main areas: products, services, and promotions. BTN Syariah Purwokerto adapts its products to local needs, enhances digital and ethical service quality, and strengthens promotions through social media and community education activities. These innovations not only improve the bank’s competitiveness but also strengthen its image as an Islamic financial institution committed to ethical values and social welfare.